PENGARUH UKURAN PERUSAHAAN, REPUTASI KAP, FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019- 2021 - Sutinah Choirotun Nissa; Tri Ratnawati (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2023)
This study aims to analyze and prove whether company size, cap reputation, and financial distress affect going-concern audit opinions in food and beverage sub-sector manufacturing companies using 75 sample companies. The sample obtained was used by purposive sampling method, namely the method of determining non-sampling sampling by providing several criteria that had been determined by the researcher. The analysis technique of this research uses Structual Equation Model – Partial Least Square (SEM-PLS) using SMART PLS Version 4.0 software. The results of this study indicate that company size, KAP reputation, financial distress have a significant effect on Going concern Audit Opinion.